Insights into the Role of Proteolytic and Adhesive Domains of Snake Venom Metalloproteinases from Bothrops spp. in the Control of Toxoplasma gondii Infection - Samuel C. Teixeira; Thales A. M. Fernandes; Guilherme de Souza; Luana C. Luz; Marina Paschoalino; Joed P. de L. Junior; Alessandra M. Rosini; Aryani F. F. Martínez; Vitor de Freitas; Daiana S. Lopes; Patrícia B. Clissa; Vinícius C. de Souza; et al. (Toxins)
Toxoplasmosis is an alarming public health problem that affects more than one-third of the world’s population. In our work, we investigated the antiparasitic effects of catalytically active [BpMP-I and Jararhagin (Jar)] and catalytically inactive [Jararhagin-C (Jar-C)] snake venom metalloproteinases (SVMPs) in human HeLa cells. These toxins impaired the parasite invasion and intracellular growth, and modulated IL-6, IL-8, and MIF cytokines that control the cell susceptibility and response against T. gondii. Furthermore, we verified that the antiprotozoal activities are not restricted to the presence of the proteolytic domain, and the adhesive domains participate in the control of T. gondii infection. Also, by analyzing the structures of Jar and Jar-C through molecular modeling and dynamics, we observed that the adhesive domains in Jar-C are more exposed due to the absence of the proteolytic domain, which could favor the interaction with different targets. Our investigation on the role of SVMP domains in combating T. gondii infection highlights their potential application as biotechnological tools for creating more effective treatments for toxoplasmosis.